If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 6 = -1y + -2 Reorder the terms: 6 + 8y = -1y + -2 Reorder the terms: 6 + 8y = -2 + -1y Solving 6 + 8y = -2 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 6 + 8y + y = -2 + -1y + y Combine like terms: 8y + y = 9y 6 + 9y = -2 + -1y + y Combine like terms: -1y + y = 0 6 + 9y = -2 + 0 6 + 9y = -2 Add '-6' to each side of the equation. 6 + -6 + 9y = -2 + -6 Combine like terms: 6 + -6 = 0 0 + 9y = -2 + -6 9y = -2 + -6 Combine like terms: -2 + -6 = -8 9y = -8 Divide each side by '9'. y = -0.8888888889 Simplifying y = -0.8888888889
| 11/1331 | | X=(y+6)(y+8) | | 75x^3+65x^2+10x=0 | | 5x+1y+0.05z=100 | | 31/2=62/t | | n/0.28=0.3/0.42 | | 18t=27(t-8) | | 16/19=p/13 | | (30/250)*5 | | 18t=17(t-8) | | 14/20=p/16 | | 8b^4(4b^3-7)= | | 14/8=28/m | | 5(x-6)=2/x | | z+5=z-7 | | 99/100*(0.4) | | 99/100*(0.4=) | | 0.30(18)+0.05x=0.15(24X) | | km+5x=6x | | 56•295/49 | | 16x^2+20x-24=0 | | 41n=-2747 | | 56*295/49= | | m(m)+4m-60=0 | | 56•295/49= | | 6n+12=x | | -3x+1+5x-4=3 | | -3/2x=21 | | -12x+10+8x=2 | | 5/9x-2/7x(-3) | | 2(3x-5)-4x=6 | | X-.833333x-4=1 |